The Development Of High Temperature Recirculating Pump (HTRP) For Energy Savings In An Incinerator. - Mohamed, N, A, H.; R., Zakaria; M, N, M,, Yunus (2004)

(untitled)
Tremendous increase ingeneration of Municipal Solid Waste (MSW) has become a major concern for the Malaysian government as the country experiencing rapid development. It was estimated about 16000 tones/day MSW is produced at national level and in Kuala Lumpur alone about 2500 tones/day.